3 d transition metal-catalyzed hydrogenation of nitriles and alkynes - Sharma, Dipesh M.; Punji, Benudhar (Chemistry-An Asian Journal, 2020)
Selective hydrogenation of nitriles and alkynes is crucial considering the vast applications of reduced products in industries and in the synthesis of bioactive compounds. Particularly, the late 3d transition metal catalysts (manganese, iron, cobalt, nickel and copper) have shown promising activity for the hydrogenation of nitriles to primary amines, secondary amines and imines. Similarly, semihydrogenation of alkynes to E- and Z-alkenes by 3d metals is adequately successful both via the transfer hydrogenation and by using molecular hydrogen. The emergence of 3d transition metals in the selective synthesis of industrially relevant amines, imines and alkenes makes this protocol more attractive. Herein, we provide a concise overview on the late 3d transition metal-catalyzed hydrogenation of nitriles to amines and imines as well as semihydrogenation of alkynes to alkenes.
Keywords: 3d transition metal; Alkynes; Hydrogenation; nitriles; Semihydrogenation